A web app for population viability and harvesting analyses. (29th November 2016) - GETZ, WAYNE M.; MUELLERKLEIN, OLIVER C.; SALTER, RICHARD M.; CARLSON, COLIN J.; LYONS, ANDREW J.; SEIDEL, DANA P.
Abstract: Population viability analysis (PVA) is used to assess the probability that a biological population will persist for a specified period of time. Such models are typically cast as Markov processes that may include age, stage, sex and metapopulation structures, density‐dependence and ecological interaction processes. They may also include harvesting, stocking, and thresholds that trigger interventions. Here we present a PVA web app that includes extensible user‐selected options. Specifically, this PVA web app allows for the specification of one to ten age classes, one or two sexes, single population or metapopulation configurations with 2 or 3 subpopulations, as well as density‐dependent settings for inducing region‐specific carrying capacities. Movement among subpopulations can be influenced by age, metapopulation connectivity, and attractivity of regions based on the relative fitness of the youngest age classes in each region. Simulations can be carried out deterministically or stochastically, with a user‐specified combination of demographic and environmental processes. This PVA web app is freely available athttp://www.numerusinc.com/webapps/pva for running directly on any browser and device. It is easily modified by users familiar with the NovaModeler Software Platform.